Relationship Between Job Satisfaction and Business Excellence:: Empirical Evidence from Hospital Nursing Departments - Tutuncu, Ozkan; Kucukusta, Deniz (Journal of Comparative International Management)

(untitled) (Management Futures, 2006)
Business excellence is important in terms of encouraging successful quality implementations, disseminating the result of such implementations to society, making quality culture widespread, creating a basis for comparison of quality implementations, and directing the quality implementer to continuous improvement. Excellence models affect performance and help organizations achieve organizational excellence. Furthermore, employee satisfaction is another concern of organizational excellence. The measurement of job satisfaction has become an important issue in TQM. In this respect, the extent to which employees are satisfied with what they are responsible for may directly influence the level of customer satisfaction with their services and products. The main purpose of the study is to determine the relationship between business excellence and job satisfaction. In order to reach this goal, a survey that contains Job Descriptive Index with 5 factors and EFQM Criteria with 6 factors is applied to different nursing departments of two research hospitals. Both hospitals are in the business excellence process. Data obtained in the study has been analyzed at the base of multivariate data analysis and the results show that the canonical correlation between job satisfaction and business excellence model is significant. Theoretical and practical implications of the findings are also discussed in the paper.